Effects of oral 3% hydrogen peroxide used as an emetic on the gastroduodenal mucosa of healthy dogs. Issue 2 (14th December 2016) - Niedzwecki, Alicia H.; Book, Bradley P.; Lewis, Kristin M.; Estep, J. Scot; Hagan, Joseph
Abstract: Objective: To characterize the extent of mucosal injury on the upper gastrointestinal tract following oral administration of 3% hydrogen peroxide (H2 O2 ) to induce emesis in normal dogs. Design: Prospective clinical study. Setting: Specialty referral hospital. Animals: Seven staff‐owned, healthy, adult dogs. Interventions: Six dogs were assigned to the H2 O2 group and 1 dog was assigned as the apomorphine control. Dogs were anesthetized for gastroduodenoscopy with gross inspection and gastroduodenal biopsies at time 0 and 4 hours, 24 hours, 1 week, and 2 weeks following administration of oral 3% H2 O2 or subconjunctival apomorphine. Gross esophageal, gastric, and duodenal mucosal lesion scoring was performed by 2 blinded, experienced scorers. Biopsy samples were evaluated histologically by a veterinary pathologist. Measurements and Main Results: Grade I esophagitis was noted in 2 dogs at 4 hours and in 1 dog at 2 weeks, while grade III esophagitis was observed in 1 dog 1 week following H2 O2 administration. At 4 hours, gastric mucosal lesions were visualized in all dogs, and lesions worsened by 24 hours. Mild to moderate duodenal mucosal lesions were visualized up to 24 hours after administration. Histopathology identified the most severe gastric lesions at 4 hours as hemorrhage; at 24 hours as degeneration, necrosis, and mucosal edema; and at 1 week as inflammation. By 2 weeks, most visual and histopathologic lesions were resolved. No histopathologic lesions were identified at any time point in the dog administered apomorphine. Conclusions: Significant visual and histopathologic gastric lesions occurred following administration of 3% H2 O2 in all dogs. Less severe visual duodenal lesions were identified. As compared to H2 O2 dogs, minimal gross gastroduodenal lesions and normal histopathology were identified in the apomorphine control.